Inter-state trade within the European Union - Jovanović Mihailo (Međunarodni Problemi)
Trade is the most important integration link in the overall world production. After the Second World War it induced the establishment of economic integrations. In the last three decades international trade has been more dynamic than the growth of the world production. The data show that the commodity trade is the strongest component of the world purchase and sale, although the international trade in services has grown a bit faster than the commodity trade. However, the share of services in the world trade does not exceed 20 per cent. International trade has most developed among developed countries, keeping up the mutual development of foreign direct investments and know-how and technology transfer. The empirical research shows that apart from the benefits gained by capitalisation of comparative advantages the trade growth is also influenced by benefits resulting from the impact of the economy of scale, competition and spreading of knowledge. Reduction of tariff and elimination of non-tariff barriers constantly opens new opportunities to benefit from international trade in commodities and services. Commodity trade of OECD countries confirms that the volume of trade does not depend only on liberalisation of tariff and non-tariff barriers, but growth to a certain degree reflects the size of the country, geographic elements and transport costs. Therefore, the empirical works predominantly analyse the power of trade as an indicator of the manifested commodity trade, embracing the characteristics such as competition pressures, but not including some deeper political meaning. The previously mentioned factor is significant, since given the policy and competition small countries are naturally more dependent on foreign trade, although competition pressures among big countries largely result from competition inside themselves. A significant change in the trade structure has been recorded in the period of over two years. At first, intra-industrial trade became equal to traditional inter- industrial production, and afterwards it has even exceeded it. For a long time the factors of foreign trade growth have been disputable. The works of Baier and Berstrand show that income growth and reduction of customs produce the main impact on foreign trade growth. In their opinion liberalisation of trade within GATT and WTO is one of the main driving forces in international trade. Reduction of trade costs also produces some impact on foreign trade growth, while approximation of incomes is less significant. Badlinger and Breuss have explored the elements that in the last four decades of the last century made an impact on faster growth of inter-trade of EU-15 member countries. They have estimated the relative impact of the income growth, income equalisation as well reduction of tariffs and trade costs on the intra-trade of EU-15 member countries. The results show that the income growth increases by 70 per cent the intra-trade of these countries. Also, the European integration and liberalisation of GATT and WTO increase by 25 per cent the commodity intra-trade of EU-15.